C-Reactive Protein (CRP) Value and Platelet Counts in Pediatric Dengue Patients at RSUP Dr. Hasan Sadikin Bandung - Irawati, Indri; Tristina, Nina; Andriyoko, Basti (Fakultas Kedokteran Universitas Brawijaya, 2024)
Plasma leakage, thrombocytopenia, and cytokines play roles in pathogenesis of dengue infection. Thrombocytopenia correlates with severity of the disease. Dengue virus infection produces cytokines that stimulate C-Reactive Protein (CRP). This study aims to describe the results of CRP and platelet counts with severity of dengue infection in paediatric inpatient at Hasan Sadikin Hospital Bandung. This is a descriptive observational study with retrospective, cross-sectional data collection in January 1-December 31, 2021 at Hasan Sadikin Hospital. From 32 total subjects, there were 24(75%) non-severe dengue infections compared to severe dengue 8(25%). Non-severe dengue 19(79.2%), had the most platelet counts of 50,000-150,000/L, while platelets count 20,000-50,000/µL was mostly in severe dengue 4/8(50%). CRP value was mostly normal (<0.3mg/dl) as many as 18/24(75%) in mild dengue, whereas in severe dengue CRP was mostly high as many as 6/8(75%). CRP examination is mostly done in critical phase, both in severe and non-severe dengue. Severe dengue infection was found mostly in platelet counts of 50,000-150,000/µL and normal CRP level as many as 14(58.3%). In severe dengue infection, platelet counts was found mostly in 20,000-50,000/µL and high CRP (≥0.3mg/dl) as many as 3(37.5%). Most cases of dengue fever infections in children at Hasan Sadikin General Hospital in 2021 were of mild severity, with platelet counts ranging from 50,000 to 150,000/µL and normal CRP levels. Examinations were typically carried out during the critical phase.